Evaluasi Program Penataan Pedagang Kaki Lima Pasar Agus Salim di Kota Pekanbaru - Nurul Azmi; Nur Laila Meilani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The existence of street vendors (PKL) is a social phenomenon that can be found in big cities. One of them is in Pekanbaru City, which is on Jalan Agus Salim. The traders who sell along Jalan Agus Salim have caused the city of Pekanbaru to become a city that is disobedient to regulations, traffic jams occur as a result of which the roads become narrower, and the environment along the roads becomes chaotic, dirty and far from healthy. The aim of this research is to determine the evaluation of the Agus Salim Market Street Vendor Arrangement Program by the Department of Trade and Industry in Pekanbaru City. This research uses Evaluation Theory according to Stufflebeam in Arikunto (2008), which uses four CIPP indicators, namely: Context, Input, Process, and Product. This type of research is qualitative research by providing an overview or descriptive problem in the form of a narrative. Collecting the necessary data, both primary data and secondary data, is collected through interviews, observation, documentation and then analyzed so that conclusions can be drawn from the existing research problem. The results of this research are evaluations which can be said to have not been optimal, because there are still inhibiting factors in its implementation, namely the lack of enthusiasm of traders to relocate and the lack of land provided for traders.